Neonatal mortality of live births with congenital diaphragmatic hernia in São Paulo State, Brazil: Failure of care? - Ana Sílvia Scavacini Marinonio; Milton Harumi Miyoshi; Daniela Testoni Costa Nobre; Adriana Sanudo; Kelsy Catherina Nema Areco; Mandira Daripa Kawakami; Rita de Cássia Xavier Balda; Tulio Konstantyner; Carina Nunes Vieira e Oliveira; Paulo Bandiera-Paiva; Rosa Maria Vieira de Freitas; Monica La Porte Teixeira; et al. (Revista Paulista de Pediatria)
ABSTRACT Objective: The aim of this study was to analyze if the healthcare organization of perinatal care and availability of referral neonatal intensive care units (NICU) impacted congenital diaphragmatic hernia (CDH) neonatal mortality in the period 2004–2020. This study analyzed the spatial distribution of neonatal deaths of live births with CDH in São Paulo State, Brazil, and its association with NICU beds’ availability. Methods: Population-based study of all live births in São Paulo State from mothers residing in the same State, from 2004 to 2020. CDH definition was based on WHO-ICD-10 codes; CDH-associated neonatal death was defined as death up to 27 days after birth of infants with CDH. The distribution of CDH-associated neonatal mortality (per 10,000 live births) and NICU beds’ availability (≥1 or not available) was mapped, and their association was evaluated by the Mann–Whitney test. Results: Among 10,246,686 live births, there were 1378 CDH-associated neonatal deaths across 124/645 (19.2%) municipalities of the State. The median CDH-associated neonatal mortality rate in municipalities with NICU beds was 1.22 (95%CI 0.99–1.51), similar to that found in municipalities with no NICU beds (1.40; 95%CI 1.15–1.67; p=0.224). Conclusions: CDH-associated neonatal deaths were spread throughout São Paulo State with no difference in CDH-associated neonatal mortality rates between municipalities with and without NICU beds available. These findings suggest the necessity of implementing regionalization strategies for CDH perinatal care in the State.